The Effect of Storytelling Using Picture Series Media on The Language Skills of Children Aged 5–6 Years at Dharma Wanita 2 Batujai Kindergarten - Latifatul Adawiyah; Gunawan Gunawan; Muhammad Tahir (Indonesian Publication Center, 2026)
This study aimed to determine the effect of storytelling using picture series media on the language skills of children aged 5–6 years at Dharma Wanita 2 Batujai Kindergarten. This study employed a quantitative approach with a pre-experimental design using a one-group pretest–posttest design. The participants consisted of 32 children aged 5–6 years who were selected using a saturated sampling technique. Data were collected through observation and documentation and analyzed using a paired-samples t-test to test the research hypothesis. The results showed that the children’s language skills improved following the implementation of storytelling using picture series media. The mean pretest score was 49.96, which increased to 69.18 in the posttest. The paired-samples t-test yielded a p-value of 0.000 (p < 0.05), indicating a statistically significant difference between the pretest and posttest scores. These findings indicate that storytelling using picture series media had a significant effect on improving the language skills of children aged 5–6 years at Dharma Wanita 2 Batujai Kindergarten. Therefore, storytelling using picture series media can be considered an alternative learning strategy to support language development in early childhood education.